A relação entre problemas de saúde mental e a aposentadoria nos idosos residentes no bairro Abolição III na cidade de Mossoró- RN - Carvalho, Anderson Araújo de (Universidade Federal Rural do Semi-Árido, 2020)
The research entitled "THE RELATIONSHIP BETWEEN MENTAL HEALTH PROBLEMS AND RETIREMENT IN ELDERLY RESIDENTS IN NEIGHBORHOOD ABOLITION III IN THE CITY OF MOSSORÓ-RN" aims to verify the real impact of retirement and its consequences in the emergence of mental health problems and in the use of psychotropics in the elderly population enrolled by the family health team of the Basic Health Unit Dr. Lucas Benjamim, from the Abolição III neighborhood, in the city of Mossoró-RN. Thus, the main unfavorable factors that contribute to the emergence of these problems in this age group can be listed and, thus, provide subsidies so that actions in the community can be created in order to mitigate such factors. It addresses the following objectives: to analyze the development of mental health problems in the elderly after their retirement; confirm the high prevalence of the use of psychotropic drugs by the elderly; to verify the relationship between retirement and the development of mental health problems; and to ascertain whether the development of mental health problems in the elderly is not necessarily due to retirement. The justification for this theme is the observation that in Brazil and in the world the growth in the number of elderly people is quite expressive, tending to reach high contingents and, among the various disorders that affect this portion of the population, mental health problems deserve special emphasis for its high prevalence, citing depression, which is considered the most found psychiatric illness among the elderly and whose prevalence is close to 15% in this population. Methodology: this is a cross-sectional study with a quantitative approach and consists of applying an question interview composed of 17 direct questions with only the options “YES” and “No” and 01 question in which the participant lists the main reason for the appearance of your problem. After that, the quantification of responses favorable to the appearance of the chart is continued, indicating the degree of the relationship as follows: less than five = weak relationship between retirement and the development of mental health problems; between 5 and 10 = moderate relationship between retirement and the development of mental health problems; greater than 10 = intense relationship between retirement and the development of mental health problems. Results: there was a moderate relationship between the development of mental health problems and retirement.
Keywords: Saúde mental; Idoso; Aposentadoria; Mental health; Seniors; Retirement; CIENCIAS DA SAUDE::MEDICINA